Nanocurcumin Release from Self-Cured Acrylic Resins; Effects on Antimicrobial Action and Flexural Strength - Parsa Soleymanijadidi; Meysam Moradi; Fahimeh Hamedirad; Zahra Ghanavati; Solmaz Maleki Dizaj; Sara Salatin (Bioengineering, 2023)
The placement of orthodontic appliances into the oral area can lead to infection, inflammatory and gingival collapse. Using an antimicrobial and anti-inflammatory material in the matrix of orthodontic appliance may help to reduce these issues. This study aimed to assess the release pattern, the antimicrobial action and the flexural strength of self-cured acrylic resins after adding different weight percentages of curcumin nanoparticles (nanocurcumin). In this in-vitro study, 60 acrylic resin samples were divided into five groups (n = 12) based on the weight percentage of curcumin nanoparticles added to the acrylic powder (0 for control, 0.5, 1, 2.5, and 5%). Then, the dissolution apparatus was used for the release assessment of nanocurcumin form the resins. For antimicrobial action assessment, the disk diffusion method was used and a three-point bending test was performed with a speed of 5 mm/min to determine the flexural strength. Data were analyzed using one-way analysis of variance (ANOVA) and Post-Hoc Tukey tests (with p < 0.05 as significant level). The microscopic images showed the homogeny distribution of nanocuricumin in self-cured acrylic resins in varied concentrations. The release pattern showed a two-step release pattern for all concentrations of nanocurcumin. The one-way ANOVA outcomes indicated that adding curcumin nanoparticles to self-cured resin increased the diameter of the inhibition zones for the groups against Streptococcus mutans (S. mutans) significantly (p < 0.0001). Additionally, as the weight percentage of curcumin nanoparticles increased, the flexural strength decreased (p < 0.0001). However, all strength values were higher than the standard value (50 MPa). No significant difference was detected between the control group and the group with 0.5 percent (p = 0.57). Considering the proper release pattern and the potent antimicrobial activity of curcumin nanoparticles, then the preparing self-cured resins containing curcumin nanoparticles can be beneficial for antimicrobial aims without damaging the flexural strength to use in orthodontic removable applications.